Real capabilities of an organization employees - E.M. Rozhdestvenskaya; P.E. Khamidov; D.P. Nepomnyashchikh (Векторы благополучия: экономика и социум)
Relevance. The real capabilities of employees in the workplace include expectations for stable earnings, opportunities for training and development, social interaction, and involvement in a shared goal. In response to these emerging needs, organizations are offering comprehensive programs to support various aspects of employee well‐being – physical and emotional health, spiritual growth, and financial management. All areas of employee well‐being are at the forefront of companies concerns. Aim. To explore how employee well‐being programs can meet real workplace needs. Methods. This research is based on Gallup's methodology, which defines well‐being in terms of five areas of functioning – career, social, financial, physical, and psychological. We employed a sociological survey using the Q12 questionnaire, with minor adaptations and adjustments. Result. The data collected allowed us to assess the well‐being of organization employees and develop strategies to improve well‐being in particular areas. The survey revealed that in each of the five areas of well‐being, there were some unmet needs that could be addressed. Conclusion. Our findings indicate that the productivity of employees is dependent on their satisfaction of real capabilities and overall well‐being. This means that it is not just about their labor rights, timely wages, or even their physical health. It also includes their mental and emotional state, as well as their social environment. Environmental factors, such as the work environment, can have a significant impact on employee performance. Therefore, organizations need to take these factors into account when developing programs to support their employees.